Design and development of an automatic ironing machine part II - Chew, Keng Kok. (2010)
Ironing is a much dreaded yet necessary household chore. This project aims to provide a low cost and fast alternative solution to ironing that requires minimal human intervention. The automated machine will be able to perform de-wrinkling tasks at a press of a button from the user.